Association among early life stress, mood features, hopelessness and suicidal risk in bipolar disorder: The potential contribution of insomnia symptoms. (March 2021) - Palagini, Laura; Miniati, Mario; Marazziti, Donatella; Sharma, Verinder; Riemann, Dieter
Abstract: Aim: The study aimed to investigate the potential pathways mediating early exposure to stressful events and the clinical manifestations of bipolar disorder (BD), such as severity of mood symptoms, hopelessness and suicidal ideation, focusing on the potential role of insomnia symptoms. Method: A sample of 162 adult participants with BD I or II were assessed during depressed phase using the Structural Clinical Interview for DSM-5 (SCID-5), the Beck Depression Inventory-II (BDI-II), the Young Mania Rating Scale (YMRS), the Early Trauma Inventory Self Report-Short Form (ETISR-SF), the Beck Hopelessness Scale (BHS), the Insomnia Severity Index (ISI) and the Scale for Suicide Ideation (SSI). Participants with or without clinically significant insomnia were compared and we carried out correlations, regression and mediation analyses. Results: Participants with insomnia showed a greater severity of depressive symptoms, of suicidal risk, of the cognitive component of hopelessness and of early life stressors. Insomnia symptoms mediated the association among early life stress and depressive symptoms (Z = 2.72, p = 0.0006), the cognitive component of hopelessness (Z = 3.02, p = 0.0001) and suicidal ideation and plans (Z = 2.07 p = 0.0006). Conclusion: Insomnia may mediate the relationship between early life stress and clinical manifestations of BD. Assessing the evolution of insomnia symptoms could offer an approach to characterize BD and to formulate treatment strategies. In particular targeting insomnia symptoms might potentially modify the clinical features of BD in response to early life stressful events.